2021
DOI: 10.1007/s11218-021-09610-5
|View full text |Cite
|
Sign up to set email alerts
|

Beyond level of self-esteem: exploring the interplay of level, stability, and contingency of self-esteem, mediating factors, and academic achievement

Abstract: Self-esteem plays a decisive role for students in achievement situations. However, it is still unclear how different self-esteem facets and their interactions influence academic achievement and which psychological mechanisms mediate these relationships. In Study 1, we investigated self-handicapping and effort-management as mediators of the effects of self-esteem facets on academic Study 2 achievement in a sample of N = 600 university students, while in we examined test anxiety as mediating variable in a sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 54 publications
(83 reference statements)
1
14
0
Order By: Relevance
“…Previous studies have always regarded academic achievement as the representative of learning outcome in general (Joksimovic et al, 2015;Sucipto et al, 2017;Nabizadeh et al, 2019;Amer, 2020). Academic performance is an objective quantitative indicator of learning outcomes (Krchner et al, 2021), which represents the achievement of teaching objectives and students' mastery of knowledge. It is worth noting that academic performance should consider not only students' examination performance but also their usual performance, such as learning enthusiasm, creativity and teamwork ability (Zhang, 2011).…”
Section: Learning Outcomesmentioning
confidence: 99%
“…Previous studies have always regarded academic achievement as the representative of learning outcome in general (Joksimovic et al, 2015;Sucipto et al, 2017;Nabizadeh et al, 2019;Amer, 2020). Academic performance is an objective quantitative indicator of learning outcomes (Krchner et al, 2021), which represents the achievement of teaching objectives and students' mastery of knowledge. It is worth noting that academic performance should consider not only students' examination performance but also their usual performance, such as learning enthusiasm, creativity and teamwork ability (Zhang, 2011).…”
Section: Learning Outcomesmentioning
confidence: 99%
“…With respect to hypothesis 1, it is confirmed that there is a direct relationship between self-esteem and resilience. The mechanisms that explain this relationship are varied, although it seems that resilience allows solving daily life problems and coping with high stress situations ( Balgiu, 2017 ), which would have an impact on a higher self-esteem ( Ferradás et al, 2020 ; Kärchner et al, 2021 ). In this sense, Servidio et al (2018) affirm that those low resilient behaviors based on problem avoidance coping strategies are precisely associated with low levels of self-esteem in line also with what was raised by ( Abdul et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Self-esteem can be defined as a person’s appraisal of his or her qualities, attributions, and expectations ( Ahmed et al, 2021 ), being of great relevance also in the academic university environment ( Ferradás et al, 2020 ). A person with high self-esteem is a person with better socioemotional and cognitive functioning ( Harun, 2017 ; Silverthorn et al, 2017 ; Kärchner et al, 2021 ). Low self-esteem seems to be related to academic problems and poor emotional adjustment in both the personal and social spheres; for this reason, it is necessary to measure it and take it into consideration ( Kärchner et al, 2021 ; Zhao and Ngai, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different dimensions of self-esteem are significantly correlated with the students' academic outcomes. However, all the dimensions of self-esteem are not directly related to students' academic outcomes but are facilitated by affective and motivational factors (Kärchner et al, 2021). Self-esteem is highly associated with students' academic performance.…”
Section: Introductionmentioning
confidence: 97%